An Algorithmic Evidence for The Relationship between Social Media Behaviour and Brand Engagement Perception of Consumers in Chennai City - Jessi , H. Hema; Chandran, M. (International Journal of Accounting and Economics Studies, 2025)
The social media engagement behaviour is considered a unified study between social media influencers on consumer buying behaviour through the powerful social media platforms like Facebook, Twitter, YouTube, and other popular social media platforms. The engagement of consumers using the content is generated by social media platforms with the aspects of following, liking, commenting, and sharing the information with other social media users on the same platform. The main aim of this research is to establish the relationship between components of social media behaviour and elements of brand engagement perception among consumers. To verify the objectives and test the hypotheses, the researcher adopted simple random sampling methods to collect 30 samples from all 15 zones of Chennai city and was able to get 437 usable samples for conducting the research. Exploratory factor analysis, confirmatory factor analysis, and structural equation model are used subsequently to verify the objectives and test the hypotheses. It is found that there is a significant relationship between social media behaviour of consumers and their brand engagement perception in any marketing arena.